Pipeline pricing and logistics planning in the refined product supply chain based on fair profit distribution. (January 2023) - Qiu, Rui; Liao, Qi; Tu, Renfu; Jiao, Yingqi; Yang, An; Guo, Zhichao; Liang, Yongtu
Highlights: Customize a bi-level programming model for the pipeline carrier and oil shipper. Propose a two-party negotiation mechanism based on fair profit distribution. Determine the pricing and logistics plan considering both benefits and fairness. Conduct a comprehensive analysis of a real case in China. Abstract: The pipeline is an economical, safe and environmentally friendly way to deliver refined products, but the uncoordinated decisions of the pipeline carrier and the oil shipper can lead to low pipeline turnover and high cross-regional logistics costs. This paper intends to remedy this problem through pipeline pricing and logistics planning. First, a framework is designed to coordinate the operational decisions of the pipeline carrier and the oil shipper. Then, a bi-level programming model is customized to characterize the decentralized decision-making process of both stakeholders, including pipeline pricing and logistics planning. The upper-level model maximizes the transportation revenue of the pipeline carrier, and the lower-level model minimizes the logistics cost of the oil shipper. The model constraints supply and demand capacity, transportation capacity, transportation network structure and mass balance. Next, to realize the coordination of both stakeholders, a negotiation mechanism based on fair profit distribution is customized. Ultimately, the method is tested on a large-scale logistics system of refined products in China. The results reveal that: (1) the pipeline turnover is increased by 127 million ton-kilometers, (2) the economic benefits of both stakeholders are maximized with an increase of 13 million CNY, (3) a fairer profit distribution is provided compared with the centralized decision-making. It is proved that the proposed method has a satisfactory coordination effect on the pricing of the pipeline carrier and the logistics planning of the oil shipper.